PEMANFAATAN PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN BENTUK LAHAN DI DAS MORAMO - Tufaila, Muh.; Karim, Jufri; Alam, Syamsu (Jurnal Agroteknos, 2012)
Research on utilization of remote sensing and geographic information system for mapping landforms in the watershed (DAS) Moramo . The research was conducted on Moramo basin, District of Moramo South Konawe . This research was conducted with image processing techniques on the image of ALOS AVNIR-2 and visual interpretation was based on analytic approach with the help of Geographic Information Systems for on screen digitizing . The research result obtained 15 (fifteen ) units of landforms, namely: Alluvial plain (F1), Alluvial Plain-Koluvial (F1.1), Flood Plain (F7), Alluvial Plain Briny Beach ( M11), Structural Terdenudasi Eroded hills Strong (D1/4), Structural Terdenudasi Eroded Hills Moderate (D1/3), Eroded Hills Terdenudasi Structural Lightweight (D1/2) , Eroded Hills Isolated Strong (D4/4), Barely Plain (peneplain) Eroded Very Lightweight (D5/1), Slope Leg Eroded hills Structural Terdenudasi Strong (D7/4), Slope Foot hills Eroded Structural Terdenudasi Medium (D7/3), Slope Foot hills Terdenudasi Eroded Structural Lightweight (D7/2), Piedmont Eroded Lightweight (D9/2), Piedmont Eroded Very Light (D9/1) and the hills Dome (Dome) Eroded Strong (S11/4). Based on their genesis, they were grouped into four landforms : marine origin, the origin of fluvial landforms, landforms denudasional origin, and the origin of structural landforms. Accuracy of landform interpretation was 89,06 % and processing of the composite image 341 had an excellent capability to identify the location of landforms in the study area of watershed Moramo. Keyword : remote sensing, GIS, watershed, image processing, landform mapping